Analisis Power Quality Sistem Kelistrikan Pada Apartemen Malang City Point - Ahmad Hermawan; Zahra Mulia Sari; Sapto Wibowo (Politeknik Negeri Malang, 2020)
The use of equipment with a high non-linear load causes a decrease in the quality of power (Power Quality) at Malang City Point Apartment. Power quality analysis is an important requirement in the electrical system and needs special attention to save energyand costs. Savings can be achieved by reducing or even eliminating losses resulting from the use of non-linear loads. This thesis aims topresent the results of an analysis of power quality conditions at Malang City Point Apartments. This analysis includes voltage, current,voltage and current imbalance, power factor, current THD and measured voltage. The system is designed using Web - Based PowerQuality Meter (PM 5110) as a measurement tool, then the results are analyzed and compared with existing standards to evaluate powerquality in Malang City Point Apartments. Among the various power quality problems measured, it was found that the main problems ofpower quality in Malang City Point Apartments were the occurrence of overvoltages and current harmonic distortion. So it is necessary todo repairs on this to overcome the overvoltage by reducing the operation of equipment that has a large load and repairing neutralconductors. Furthermore, to reduce the system harmonics, it is designed by designing a single tuned passive filter and simulated using theETAP software version 16.0.0